Intelligent Virtual Agents 8th International Conference, IVA 2008, Tokyo, Japan, September 1-3, 2008, Proceedings - Prendinger, Helmut; Lester, James; Ishizuka, Mitsuru (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the refereed proceedings of the 8th International Workshop on Intelligent Virtual Agents, IVA 2008, held in Tokyo, Japan, in September 2008. The 18 revised full papers and 28 revised short papers presented together 42 poster papers were carefully reviewed and selected from 99 submissions. The papers are organized in topical sections on motion and empathy; narrative and augmented reality; conversation and negotiation; nonverbal behavior; models of culture and personality; markup and representation languages; architectures for robotic agents; cognitive architectures; agents for healthcare and training; and agents in games, museums and virtual worlds.